Structural Sources of Intraorganizational: Power: A Theoretical Synthesis - Astley, W. Graham; Sachdeva, Paramjit S. (Academy of Management Review, 1984)
Research on organizational power has become overly fragmented; a multitude of different sources of power have been identified. Consequently, an overall picture of intraorganizational power relations is difficult to obtain. In this paper, three structural sources of power—hierarchical authority, resource control, and network centrality—are integrated in a theoretical synthesis. The complex nature of intraorganizational power is revealed in the interactions, tensions, and conflicts among the three sources of power.